2013
DOI: 10.1002/2013ja019277
|View full text |Cite
|
Sign up to set email alerts
|

Intensities of the Venusian N2 electron‐impact excited dayglow emissions

Abstract: [1] Dayglow emissions are signatures of both the energy deposition into an atmosphere and the abundances of the species from which they arise. The first N 2 dayglow emissions from Mars, the (0,5) and (0,6) bands of the N 2 Vegard-Kaplan band system, were detected by the Spectroscopy for Investigations of the Characteristics of the Atmosphere of Mars (SPICAM) UV spectrometer on board the Mars Express spacecraft. The Vegard-Kaplan band system arises from the transition from the lowest N 2 triplet state (A 3 † + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Their presence was confirmed and the N 2 LBH bands were also detected with MAVEN/IUVS (Stevens et al 2015) but no N 2 emission has been observed so far on Venus. Fox and Hać (2013) predicted the overhead intensities of 17 N 2 band systems and limb profiles of the Vegard-Kaplan bands. They expected that the Venus N 2 emissions are 5.5-9.5 times stronger than those of Mars, as the N 2 mixing ratio is larger in the Venus thermosphere and because the solar flux is about four times greater at the orbit of Venus than that at Mars.…”
Section: Far Ultravioletmentioning
confidence: 99%
“…Their presence was confirmed and the N 2 LBH bands were also detected with MAVEN/IUVS (Stevens et al 2015) but no N 2 emission has been observed so far on Venus. Fox and Hać (2013) predicted the overhead intensities of 17 N 2 band systems and limb profiles of the Vegard-Kaplan bands. They expected that the Venus N 2 emissions are 5.5-9.5 times stronger than those of Mars, as the N 2 mixing ratio is larger in the Venus thermosphere and because the solar flux is about four times greater at the orbit of Venus than that at Mars.…”
Section: Far Ultravioletmentioning
confidence: 99%